2001
DOI: 10.1211/0022357011775262
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, vitamin C and dithiothreitol, activate membrane-bound guanylate cyclase in PC12 cells

Abstract: Antioxidants and antioxidant enzymes are known to protect against cell death induced by reactive oxygen species. However, apart from directly quenching free radicals, little is known about the effect of antioxidants on hormone-activated second messenger systems. We previously found that antioxidants such as 17-beta estradiol and resveratrol activate membrane-bound guanylate cyclase GC-A, the receptor for atrial natriuretic factor (ANF), in PC12 cells. It is possible that other antioxidants may also activate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Resveratrol activates membrane-bound guanylate cyclase GC-A, the receptor for atrial natriuretic factor (ANF) [95]. At molecular level, the cGMP/kinase-G is an antiproliferative signaling in SMCs and it dilates blood vessels through the reduction of intracellular calcium.…”
Section: Resveratrol and Vasorelaxationmentioning
confidence: 99%
“…Resveratrol activates membrane-bound guanylate cyclase GC-A, the receptor for atrial natriuretic factor (ANF) [95]. At molecular level, the cGMP/kinase-G is an antiproliferative signaling in SMCs and it dilates blood vessels through the reduction of intracellular calcium.…”
Section: Resveratrol and Vasorelaxationmentioning
confidence: 99%
“…However, it was surprising that vitamin C reduced relaxations to acetylcholine and DEA-NONOate in C57BL/6J mice. Measurements of cGMP levels in arterial wall indicated that vitamin C significantly increased concentration of nitric oxide second messenger (Chen et al, 2001). This effect was selective for cGMP because cAMP levels were not affected.…”
Section: Fig 5 Bar Graphs Showing Basal Cgmp (A)mentioning
confidence: 99%
“…The cell extracts were scraped and centrifuged for 15 min at 2000 g, and the supernatant fractions were extracted with water-saturated ether to remove trichloroacetic acid. The cGMP levels in the supernatants were determined by radioimmunoassay (Chang & Song 1993;Chen et al 1998Chen et al , 2000Chen et al , 2001a.…”
Section: Methodsmentioning
confidence: 99%
“…Reactions were initiated by the addition of LLC-PK1 cell membranes, incubated for 10 min and terminated by the addition of 0.5 mL 50 mM chilled sodium acetate, pH 4.0. Generated cGMP was quantified by the radioimmunoassay as previously described (Chang & Song 1993;Chen et al 1998Chen et al , 2000Chen et al , 2001a.…”
Section: Guanylate Cyclase Assaymentioning
confidence: 99%
See 1 more Smart Citation